Guest Online Review: An Extraordinary Focus on Hotel Users' Satisfaction, Engagement, and Loyalty. Issue 4 (4th July 2022) - Vo, Nga Thi; Hung, Vo Viet; Tuckova, Zuzana; Pham, Nhat Tan; Nguyen, Lien H. L.
ABSTRACT: The article aims to heighten the impact of guest online reviews on the hotel industry. Its objective is to increase the volume of users on the degree of satisfaction for effective engagement and loyalty in the luxury hotel context. Based on a keyword-driven search, the study has examined the factors influencing the guest online reviews: guest feedback, hotel management response, and customer decision-making process. They, in turn, impact the levels of customer satisfaction and engagement in the hotel and tourism industry in Vietnam. The practical problem takes place when there is a decline in the number of customers. Particularly hotel management is involved in facing negative comments in the online market. The quantitative method tested the validity of the measurements of the questionnaire and the correlation of the constructs through SPSS tools. Three hundred and eighty-four respondents participated in the survey, who are associating with the hotel and tourism profession. The results show that the customer's decision-making process holds the most significant impact in guest reviews' online activity toward the hoteliers' service quality to create positive customer satisfaction in handling online communication. The study's implications are to foster luxury hotel management and sustainable tourism by adopting guest online reviews in developed and developing countries. Its limitation and further study are also discussed to an overall understanding of existing and future research.